Female spectators as customers at National Football League games. Issue 2 (29th April 2016) - Harrison, C. Keith; Bukstein, Scott; McPherson Botts, Ginny; Lawrence, Suzanne Malia
Abstract : Purpose: – The purpose of this paper is to investigate female National Football League (NFL) spectators' preferences and feedback in regard to various customer service components of the NFL game day experience. The primary components with respect to female spectators' choices, preferences, and feedback are as follows: apparel and other merchandise; food and beverage; restrooms and facility cleanliness; tailgating and parking; participants' decision to attend an NFL game; and participants' perceptions of the NFL. A core objective was to learn more about the female decision-making process and overall experience at NFL games. Design/methodology/approach: – All data were collected during the 2012-2013 NFL regular season. Four different data collections were conducted at two NFL stadiums to investigate the game day experiences of women at NFL games. Previous research was used as a basis for creating survey questions about the female game day experience. In this study, an open-ended questionnaire contained both quantitative and qualitative questions, both forms of data were collected and analyzed, and researchers made both quantitative and qualitative interpretations based on the data. Findings: – Findings and results indicated women are diverse customers. Sport organizations need to focus on the minor details that reflect how individuals experience a brand and product, as these sport organizations have the opportunity to enhance the female customer experience and retain existing female customers if the organizations systemically listen to and communicate with the female customer at NFL games. The NFL and individual NFL teams should include female spectators in the brand strategy process. Female customers of the NFL can be powerful brand loyalists and outstanding brand ambassadors. Originality/value: – This research study provides an investigation of the preferences and perceptions of women spectators at NFL games. One contribution of the current study is that researchers have accepted the challenge by some researchers calling for more complexity with researching gender and attempting to shift some of the ways in which women are viewed as fans and spectators. However, what is key with the approach in the current study is that researchers allowed the women to be heard with respect to their game day experiences, perceptions, and thoughts about their identity as a spectator.